How Managers Can Reduce Household Water Use Through Communication: A Field Experiment. (20th August 2020) - Hodges, Heather; Kuehl, Colin; Anderson, Sarah E.; Ehret, Phillip J.; Brick, Cameron
Abstract: As populations increase and droughts intensify, water providers are using tools such as persuasive messaging to decrease residential water use. However, district‐led messaging campaigns are rarely informed by psychological science, evaluated for effectiveness, or strategically disseminated. In collaboration with a water district, we report a field experiment among single‐family households using persuasive messaging based on the information‐motivation‐behavioral skills model (IMB). We randomly assigned 10, 000 households to receive different mailings and measured household water use. All messaging reduced water consumption relative to the control. On average, water use dropped 0.68 hundred cubic feet (HCF) (509 gallons) per household in the first month. Had all 10, 000 single‐family, occupied, non‐agricultural residences been mailed the IMB messaging, more than five million gallons would have been saved in the first month. The effects declined but persisted for approximately three months and were three to six times greater in households with high water use (75th to 90th percentiles) relative to average water use. These findings suggest that combining message elements from the IMB model can reduce residential water use and that targeting high‐use households is particularly cost‐effective.